Experimental Evaluation of a Vacuum-Assisted Solar Still for Improved Desalination Efficiency - Muftah , Ali; Elayb, Anas; Abugadura, Mabrouk; Almadhoni, Khalid (Sharwes Scientific Journal, 2025)
The worsening challenge of accessing freshwater and the rising cost of energy required for its production through conventional desalination methods have intensified research efforts toward utilizing solar energy for seawater desalination. This study focuses on enhancing the performance of a solar still by integrating it with a vacuum-assisted system to create partial vacuum conditions inside the still. The modified design incorporates a closed-loop water circulation system equipped with a Venturi tube to reduce internal pressure, which in turn lowers the evaporation temperature and increases freshwater output. Field experiments were conducted under both atmospheric and reduced-pressure conditions, evaluating the effects of basin water depth, ambient temperature, and wind speed. The results showed up to a 30% increase in productivity under vacuum conditions, especially at higher water depths. These findings highlight the potential of low-cost, vacuum-enhanced solar stills for off-grid freshwater production in arid regions